A public health approach to preventing child maltreatment: An intelligent information infrastructure to help us know what works. (August 2020) - Malvaso, Catia; Pilkington, Rhiannon; Montgomerie, Alicia; Delfabbro, Paul; Lynch, John
Abstract: Researchers and policymakers have called for a shift from incident-driven statutory child protection responses to greater investment in coordinated system-wide child and family focused approaches to preventing child maltreatment. However, system-wide capacity to prevent maltreatment is limited without an intelligent information infrastructure that is able to routinely examine child and family focused outcomes, and overall system performance to increase our understanding of what works. The purpose of this article is to investigate the current state of indicators for child protection, health, development and wellbeing, and to propose indicator domains that are needed for an intelligent information infrastructure in a prevention-focused child protection system. A non-systematic narrative review was undertaken to explore commonly used indicators. Examples are drawn from high-income countries with well-developed child protection agencies. Our analysis shows that process indicators that measure within-agency activities are most commonly used. Indicators that measure outcomes in children are less common, and even less common are indicators linking system processes to child and family outcomes. Capacity to understand the success of system-wide prevention of child maltreatment is limited by siloed data collection and information systems. Three information indicator domains need to be routinely collected and linked. First, within-agency processes (what activities occurred); second, warm handover (referrals between agencies) and therapeutic dose of interventions; and third, child and family wellbeing outcomes. An intelligent information infrastructure spanning these domains would increase capacity to understand whole-of-system efforts to prevent child maltreatment.